Optimization of HPMC and Na-CMC as Gelling Agents on Physical Properties and Stability in Sunflower Seed Oil Gel Formulation - Putri Rahmani , Sanubari Indah; Zulkarnain, Abdul Karim (Journal of Food and Pharmaceutical Sciences, 2023)
Abstract: In recent years, skincare with natural ingredients is being developed for it has fewer side effects and is relatively suitable for all skin types. One of the potential ingredients from the natural ingredients is sunflower seed oil, which has proven to have potential as a skin moisturizer and fight acne bacteria. The purpose of this study was to make a gel formulation of sunflower seed oil by optimizing the combination of the gelling agent of HPMC and Na-CMC. The Simplex Lattice Design method was used to optimize the gel base with Design Expert software version 13. There were 8 gel formulas made and evaluated including organoleptic, homogeneity, pH, viscosity, spreadability, and adhesion. The independent variables in SLD were the amount of HPMC and Na-CMC, while the responses included pH, viscosity, and spreadability. The optimal formula suggested by SLD is a combination of 1.451% HPMC and 1.549% Na-CMC. The optimal formula has a pH of 6.813 ± 0.041, a viscosity of 194.8 ± 2.94 dPas, an adhesion of 6.29 ± 0.50 seconds, and a spreadability of 21.5 ± 10.05 cm2. The optimum prediction formula from the software has no significant difference from the test results which show that the method can be used to predict the physical properties of sunflower seed oil gel preparations. The results of the physical stability test also stated that its physical properties were stable in terms of pH, viscosity, spreadability, and adhesion.